2020
DOI: 10.1152/ajpendo.00265.2019
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and diet-related changes in the maternal gut microbiota following exposure to an elevated linoleic acid diet

Abstract: Dietary intakes of linoleic acid (LA) have increased, including in women of reproductive age. Changes in maternal gut microbiome have been implicated in the metabolic adaptions that occur during pregnancy. We aimed to investigate whether consumption of a diet with elevated LA altered fecal microbiome diversity before and during pregnancy. Female Wistar-Kyoto rats consumed a high-LA diet (HLA: 6.21% of energy) or a low-LA diet (LLA: 1.44% of energy) for 10 wk before mating and during pregnancy. DNA was isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
3
9
0
Order By: Relevance
“…Alpha-linolenic acid (ALA) has a significant regulatory effect on the gut microbiota of mice fed a high-fat diet [ 28 ]. In addition, dietary linoleic acid (LA) altered fecal microbiome diversity before and during pregnancy [ 29 ]. It has been hypothesized that these fatty acids could exert their reductive effects on Cd accumulation by sustaining some key members of the gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Alpha-linolenic acid (ALA) has a significant regulatory effect on the gut microbiota of mice fed a high-fat diet [ 28 ]. In addition, dietary linoleic acid (LA) altered fecal microbiome diversity before and during pregnancy [ 29 ]. It has been hypothesized that these fatty acids could exert their reductive effects on Cd accumulation by sustaining some key members of the gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…This is even more true when examining the effect of maternal dietary n -6 PUFA in a moderate fat diet during gestation and lactation on host–microbiota interactions. In a recent study, Shrestha et al demonstrated that a high consumption of LA (6.2% of energy) in a normal fat diet (9% of energy) does not significantly alter the gut microbiota composition of dams during pregnancy as compared to a lower intake of LA, but they did not investigate the offspring microbiota [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we identified that plasma levels of omega-3 and omega-6 oxylipins are negatively associated with the relative abundance of the Sutterella genus in feces. In line with these results, rats consuming a diet rich in the omega-6 PUFA LA for 10 weeks showed a decrease in the relative abundance of the Sutterella genus [ 35 ]. In contrast, daily oral supplementation with omega-3 PUFAs (i.e., 4 g of EPA and DHA) for eight weeks increased the relative abundance of Sutterellaceae family in feces of in middle-aged healthy humans [ 36 ].…”
Section: Discussionmentioning
confidence: 68%